Analysis of nutrition clinical studies involving children in the Middle East and globally. (31st July 2018) - Ozdener, Fatih; Kirbiyik, Feza; Dogan, Ali Evrim
Aim: To assess pediatric clinical nutrition research by analyzing clinical studies in the Middle East (ME) and globally.Methods: UsingClinicalTrials.gov, the numbers of clinical studies in the ME and globally were analyzed.Results: The majority of clinical nutrition trials are in North America and Europe. The ME accounts for 4% of all nutrition trials. The majority of pediatric nutrition studies in the ME are in the later phases or are observational and/or epidemiological studies with a focus on poor nutrition or nutrition disorders. Industry funding in the ME is mostly by regional or local companies; few major global companies are involved.Conclusion: The ME is not well represented in clinical nutrition studies involving children. Effort should be expended to rectify this. Lay abstract: Nutritional disorders have become an important worldwide disease burden during the last several decades. The development of effective therapies for nutritional disorders requires clinical trials in the affected populations. Our results showed that although the Middle East currently has the highest proportion of children worldwide, it is not well represented in clinical trials on nutritional studies in children. Furthermore, there is suboptimal funding from the multinational nutrition industry. This analysis indicates that there is a reasonable rationale for inclusion of the Middle East in nutritional clinical research in children, and that there is an untapped opportunity for the expansion of clinical research in this region.